1995
DOI: 10.1063/1.113254
|View full text |Cite
|
Sign up to set email alerts
|

Low thermal budget insitu removal of oxygen and carbon on silicon for silicon epitaxy in an ultrahigh vacuum rapid thermal chemical vapor deposition reactor

Abstract: Articles you may be interested inLow temperature silicon epitaxy in an ultrahigh vacuum rapid thermal chemical vapor deposition reactor using disilane Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Such temperatures are often unacceptable if the pre-existing devices have dopant profiles. Pre-cleaning process with low thermal budget has been studied by many groups [9][10][11]. Recently, Carroll et al [11] has achieved a carbon-free and oxygen-free silicon surface with hydrogen baking at 800°C, upon which SiGe was then grown.…”
Section: Silicon Epitaxial Regrowth On Strained Sigementioning
confidence: 99%
“…Such temperatures are often unacceptable if the pre-existing devices have dopant profiles. Pre-cleaning process with low thermal budget has been studied by many groups [9][10][11]. Recently, Carroll et al [11] has achieved a carbon-free and oxygen-free silicon surface with hydrogen baking at 800°C, upon which SiGe was then grown.…”
Section: Silicon Epitaxial Regrowth On Strained Sigementioning
confidence: 99%
“…Indeed, less carbon is observed for higher hydrogen pressure bakes, however, it is also observed that carbon was removed from the silicon surface for high hydrogen pressures, 10 and 250 Torr, at 800ЊC. Two proposed mechanisms of carbon removal from the silicon surface during hydrogen baking at temperatures around 800ЊC are either desorption of carbon as hydrocarbons or methysilanes, 4,28 or diffusion of carbon from the surface into the silicon bulk. 26 However, further analysis of these two possible mechanisms goes beyond the scope of this work due to limits of SIMS resolution (i.e., SIMS broadening and detection limits) and an incomplete knowledge of how much carbon is desorbed into the hydrogen atmosphere.…”
Section: Sims Measurements This Cleaning Technique (800њc 2 Min 10mentioning
confidence: 99%
“…700-800ЊC bakes in hydrogen.-The complete removal of oxygen and carbon from silicon surfaces before epitaxy by baking in hydrogen atmospheres at higher temperatures (750-850ЊC) has been previously reported for UHV-CVD. 4,28 Their success has been attributed to low oxygen and water-vapor partial pressures, below the critical levels required for clean silicon surfaces in a vacuum at a given temperature. 29,30 References 4 and 28 stressed the importance of both the UHV system and the hydrocarbon-free "dry" load-lock system.…”
Section: Contamination From Reactor Load-lock and Laboratorymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most critical steps in such thin film SOI device fabrication is the silicon selective epitaxial growth (SEG) which is mandatory for the formation of Raised Sources and Drains [8][9][10][11]. A traditional epitaxial growth process consists first of all of a ''HF-last'' ex situ wet cleaning, resulting in a hydrogen terminated surface with a sub-monolayer coverage by oxygen, fluor and carbon atoms [12], a high-temperature in situ cleaning, used to form an atomically clean Si surface fit for some epitaxial growth and finally a chemical vapour deposition (CVD) step. This in situ cleaning is often accomplished through an H 2 bake at elevated temperature (T4850 1C), which is very effective in removing the remaining contaminants [11,13].…”
Section: Introductionmentioning
confidence: 99%